2018
DOI: 10.1249/mss.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Responses of Appetite to Acute Exercise

Abstract: Our replicated crossover study allowed, for the first time, the interaction between participant and acute exercise response in appetite parameters to be quantified. Even after adjustment for individual baseline measurements, participants demonstrated individual differences in perceived appetite and hormone responses to acute exercise bouts beyond any random within-subject variability over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Furthermore, using the "gold standard" replicated crossover study design (Atkinson and Batterham, 2015;Senn, 2016), we have demonstrated recently the presence of true interindividual heterogeneity in appetite perceptions and circulating concentrations of acylated ghrelin, total PYY, insulin and glucose in response to a standardised meal, over and above any random within-subject variability and measurement error (Goltz et al 2019). Similar findings were also observed in acylated ghrelin, total PYY and perceived appetite responses to replicated single bouts of aerobic exercise (Goltz et al 2018).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, using the "gold standard" replicated crossover study design (Atkinson and Batterham, 2015;Senn, 2016), we have demonstrated recently the presence of true interindividual heterogeneity in appetite perceptions and circulating concentrations of acylated ghrelin, total PYY, insulin and glucose in response to a standardised meal, over and above any random within-subject variability and measurement error (Goltz et al 2019). Similar findings were also observed in acylated ghrelin, total PYY and perceived appetite responses to replicated single bouts of aerobic exercise (Goltz et al 2018).…”
Section: Introductionsupporting
confidence: 58%
“…Interestingly, no statistically significant associations between fasting or postprandial perceived overall appetite and acylated ghrelin or total PYY were identified. Even though circulating concentrations of acylated ghrelin and PYY vary on a mealto-meal basis, concomitantly with perceived appetite, the magnitude and direction of the changes in hormone concentrations are not always mirrored by changes in perceived appetite (Goltz et al 2018). In contrast, postprandial overall appetite AUC was positively associated with postprandial insulin AUC in women, which is consistent with previous findings showing that postprandial insulin concentrations are positively associated with postprandial satiety and negatively associated with postprandial hunger (Flint et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we utilized a purely statistical procedure to calculate the smallest worthwhile difference in its place. While this procedure has been recommended as an alternative and successfully used elsewhere, it remains possible that a true MCID would differ from the number we generated, thus altering the interpretation of our results. Additionally, other parameters for evaluating glucose tolerance and glycemic control, such as fasting glucose, glycated hemoglobin, or area under the curve of the OGTT, were not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the blood glucose lowering response to exercise training in T2DM may not only exhibit inter-individual variability but also intra-individual variability of the measurement if the intervention was repeated within an individual. Consequently, the optimal approach for quantifying inter-individual variability in repeated-measures studies is to use a randomized replicated crossover design where the control (no training) and treatment (training) conditions are administered to each participant at least twice ( Senn et al, 2011 ; Hecksteden et al, 2015 ; Atkinson et al, 2018 ; Goltz et al, 2018 ) ( Figure 2 ). This design would allow accurate interpretation of a significant patient-by-treatment interaction, thereby revealing the true individual differences in response to exercise.…”
Section: How Should We Quantify Inter-individual Variability and Thermentioning
confidence: 99%